Stability assessment of sulphur (II) compounds in medicinal water from B-8b Michał intake in Busko-Zdrój - Lipiec, Iwona; Rusiniak, Piotr (Bulletin of Geography. Physical Geography Series, 2020)
In this paper, the stability of sulphur (II) compounds determined as the sum of hydrogen sulphide, hydrosulphides and sulphides was evaluated in groundwater sourced from the B-8b Michał intake. Sulphide waters are a valuable raw material used as a basis for spa treatment in Busko-Zdrój. Based on the chemical composition analyses conducted in the years 1946–2018, a general analysis of random variability and statistical analysis of data was performed using PS IMAGO 5.0.1 software. Stability assessment was carried out on the data set for the 2009–2018 period on the basis of individual measurement control charts. Trend analysis was also performed using the GWSDAT software.